Safety of Dam Structures from Ground Vibrations Due to Demolition Blasting of Coffer Wall of a Hydroelectric Project in India. (January 2015) - Roy, Pijush Pal; Sawmliana, Chhangte; Singh, Rakesh K; Mukhiya, Ramesh
The National Hydroelectric Project Corporation (NHPC) Limited, a Government of India Undertaking, while constructing a 132 MW Hydroelectric Project on the river Teesta at the district of Darjeeling in West Bengal built one concrete coffer wall on the upstream of the river to facilitate the construction of barrage and spillway. One end of the coffer wall was abutted to the barrage pier and the other end to the left bank onto the cellular wall. The demolition of the said coffer wall by controlled blasting was entrusted to CSIR-CIMFR by NHPC. The paper deals with the scientific methodology resorted by CSIR-CIMFR for accomplishing the job successfully with full safety to the nearby structures viz. barrage, spillway, Intake, penstocks, surface powerhouse, tail channel, pot head yard etc.